2022
DOI: 10.21203/rs.3.rs-1553020/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radicals scavenging potentials and mosquito vectors’ bio-control measures from bioactive principles of the marine red algae Porteria hornemannii

Abstract: This study investigated the presence of phytochemicals, yield of extract, total phenol and flavonoids content of the red seaweed Porteria hornemannii. For the extraction of metabolites from P. hornemannii, two different solvents like methanol and chloroform were used. In the phytochemical test, the methanol extract of P. hornemannii (MEPH) showed superior results in comparison with chloroform. After the crude methanol extract is purified by 86%, it is subjected to a quantitative method which, respectively, det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…stephensi was investigated and larvicidal effects were detected in all extracts applied to all species ( Table 2 ). Furthermore, the methanol extracts were found to have significantly higher toxicity than the chloroform extracts ( Arumugam et al, 2022 ). According to the results of GC-MS analysis of P. hornemannii methanol extract, it was reported that the substance with 41.88% content was n-hexadecanoic acid, which Sigamani et al (2020) showed as the source of high larvicidal effect on mosquito.…”
Section: Resultsmentioning
confidence: 99%
“…stephensi was investigated and larvicidal effects were detected in all extracts applied to all species ( Table 2 ). Furthermore, the methanol extracts were found to have significantly higher toxicity than the chloroform extracts ( Arumugam et al, 2022 ). According to the results of GC-MS analysis of P. hornemannii methanol extract, it was reported that the substance with 41.88% content was n-hexadecanoic acid, which Sigamani et al (2020) showed as the source of high larvicidal effect on mosquito.…”
Section: Resultsmentioning
confidence: 99%